Information Theory Consequences of the Scale-Invariance of Schröedinger’s Equation - Angel Ricardo Plastino; Angelo Plastino; Silvana Flego (Entropy, 2011)
In this communication we show that Fisher’s information measure emerges as a direct consequence of the scale-invariance of Schröedinger’s equation. Interesting, well-known additional results are re-obtained as well, for whose derivation only (and this is the novelty) the scale invariance property is needed, without further ado.